INNOVATION STRATEGY TO IMPROVE THE COMPETITIVENESS OF MICRO, SMALL, AND MEDIUM ENTERPRISES OF BANDAR LAMPUNG BANANA CHIPS - Hartami Dewi; Mohamad Syamsul Maarif; Titi Candra Sunarti (School of Business, IPB University (SB-IPB), 2017)
Innovation is needed by micro, small, and medium enterprises to grow and develop into large businesses. However, that innovations are limited by existing constraints such as limited number of employees, total assets, total revenues and total budget for innovation. Human resources or the entrepreneur is known to be an important factor in improving the performance and innovation of SMEs or UMKM. This research aims to formulate strategies given the constraints of innovation, human resource capacity and opportunities for innovation in improving competitiveness. The analytical method used is confirmed method, the evaluation model of structural equation modeling (SEM) and the analytic hierarchy process (AHP). The analysis showed an effect of human resources amounting to 0.761 on the settlement of the constraints and influence of 0.806 to successful innovation. The main obstacle that have to be resolved are human resources, promotion, managerial finance and administration, location, and marketing. The innovation that most influence in purchasing decisions and according to the ability of SMEs are service innovation, organization, business model, supply chain, and marketing. The best strategy formulation that can be done in improving the competitiveness of businesses are participation in exhibitions and entrepreneurship seminars, technical assistance, training and the online marketing promotion, as well as the provision of machinery and appropriate process equipment.Keywords: innovation, competitiveness, structural equation modeling, analytic hierarchy process